Other Malays nationalism and cosmopolitanism in the modern Malay world - Kahn, Joel S. (Southeast Asia publications series, 2006)
The narrative of Malay identity devised by Malay nationalists, writers, and filmmakers in the late colonial period associated Malayness with the village (kampung), envisaged as static, ethnically homogenous, classless, indigenous, subsistence-oriented, rural, embedded in family and community, and loyal to a royal court. Joel Kahn challenges the kampung version of Malayness, arguing that it ignores the immigration of Malays from outside the peninsula to participate in trade or commercial agriculture, the substantial Malay population in towns and cities, and the reformist Muslims who argued for a common bond in Islam and played down Malayness